2019
DOI: 10.1111/1751-2980.12750
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of fecal microbiota transplant in 9 critically ill patients with severe and complicated Clostridium difficile infection with impending colectomy

Abstract: Objective: Significant data support the efficacy and safety of fecal microbiota transplant (FMT) in recurrent Clostridium difficile infection (CDI). The objective of our study was to determine the success rate of FMT in patients diagnosed with severe and complicated CDI with impending colectomy in the intensive care setting.Methods: This was a 2-center study of 9 patients who met the criteria for severe and complicated CDI and had an impending colectomy. All 9 patients had failed conventional antibiotic therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
2
19
0
1
Order By: Relevance
“…100% (2/2) of abdominal pain, 86.7% (13/15) of diarrhea, 69.2% (9/13) of abdominal distention, and 50% (1/2) of hematochezia can be alleviated by FMT. These results were similar to those of a recent case series which included nine critically ill patients with severe CDI [30]. It indicated that following FMT there was marked improvement in clinical status with resolution of diarrhea and reduction in abdominal distention and pain [30].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…100% (2/2) of abdominal pain, 86.7% (13/15) of diarrhea, 69.2% (9/13) of abdominal distention, and 50% (1/2) of hematochezia can be alleviated by FMT. These results were similar to those of a recent case series which included nine critically ill patients with severe CDI [30]. It indicated that following FMT there was marked improvement in clinical status with resolution of diarrhea and reduction in abdominal distention and pain [30].…”
Section: Discussionsupporting
confidence: 88%
“…These results were similar to those of a recent case series which included nine critically ill patients with severe CDI [30]. It indicated that following FMT there was marked improvement in clinical status with resolution of diarrhea and reduction in abdominal distention and pain [30]. Alleviation of these abdominal symptoms may improve life quality of the critically ill patients and provided chances for other treatments.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the utility of FMT in severe or fulminant CDI, especially for critically ill, hospitalised patients, is not well described in the current literature. While there have been several publications demonstrating FMT to be safe and effective in this population, much of this data is uncontrolled and does not directly compare patients who received antibiotics plus FMT vs antibiotics alone (standard of care, SOC) . The aim of this study was to assess the outcomes of hospitalised patients with severe or fulminant CDI requiring intensive care who received antibiotics plus FMT compared to SOC.…”
Section: Introductionmentioning
confidence: 99%
“…For refractory CDI, even though exclusion of other causes is required (for example ulcerative colitis, microscopic colitis), FMT as rescue treatment appears encouraging, although few studies have addressed the effects of FMT in patients with refractory or severe CDI [32][33][34][35][36][37]. Furthermore, FMT appeared to decrease mortality in patients with severe CDI refractory to antibiotic therapy [34][35][36]38], and could also be considered as a therapeutic option for this condition, with decision taken on a case-by-case basis.…”
Section: Which Patients With CDI Should Be Considered For Fmt?mentioning
confidence: 99%